Enhancing thermophilic anaerobic co-digestion of sewage sludge and food waste with biogas residue biochar. (April 2022) - Liu, Hongbo; Wang, Xingkang; Fang, Yueying; Lai, Wenjia; Xu, Suyun; Lichtfouse, Eric
Abstract: Biochar addition to anaerobic digestion systems generally improves the conversion of organic waste into methane, yet biogas residues are still unwanted byproducts that may pollute the environment. Therefore, we hypothesized that biogas residues could be recycled into new biochar. We produced biochar by heating at 500 °C the residue of anaerobic digestion of food waste. We measured methane production by adding either this residue biochar, or coconut shell biochar, or corn stalk biochar, in the anaerobic co-digestion of sewage sludge and food waste. Results show that the residue biochar produces the highest daily methane amount, of 432.2 mL per g of volatile solids, versus 377.7–386.3 mL for coconut and corn biochars. This finding is tentatively explained by the fact that the residue biochar has more basic groups, which neutralize fatty acids and, in turn, alleviates acidification. Another explanation is the higher abundance in sludge of electroactive Clostridia, Methanobacterium and Methanobrevibacter, which are known to accelerate methanation. Recyling biogas residues as biochar onsite would both decrease the amount of digestion byproducts and avoid long-distance transportation of biochar from remote biomass. Graphical abstract: Image 1 Highlights: Biochar was prepared from biogas residue in a new way. A new recycling model was established coupling biochar with AD. Biogas residue biochar increased methane yield of AD. Biogas residue biochar improved enzyme activity and shortened the lag phase time. Biogas residue biochar changed the methanogenic community structure of AD.